Energy Conditions for Hamiltonicity of Graphs - Guidong Yu; Gaixiang Cai; Miaolin Ye; Jinde Cao (Discrete Dynamics in Nature and Society)
Let G be an undirected simple graph of order n. Let A(G) be the adjacency matrix of G, and let μ1(G)≤μ2(G)≤⋯≤μn(G) be its eigenvalues. The energy of G is defined as ℰ(G)=∑i=1n‍|μi(G)|. Denote by GBPT a bipartite graph. In this paper, we establish the sufficient conditions for G having a Hamiltonian path or cycle or to be Hamilton-connected in terms of the energy of the complement of G, and give the sufficient condition for GBPT having a Hamiltonian cycle in terms of the energy of the quasi-complement of GBPT.